Penerapan Metode Tutor Sebaya Dalam Pembelajaran Matematika - Rizky Kurniawan; Nana Hendracipta; Reksa Adya Pribadi (Coopetition : Jurnal Ilmiah Manajemen, 2023)
This study aims to find out how the peer tutoring method is applied in learning Mathematics which is applied by fifth grade teachers at SDN Kalideres 07. The purpose of this study is to describe the application process and the results of applying the peer tutoring method. This research uses a qualitative approach with descriptive methods. The data collection process was carried out using interview, observation, and documentation techniques. The results of this study indicate that the application of the peer tutoring method in learning mathematics can increase interaction between students during the activity. Tasks that are difficult to do will be carried out together with the help of students who become tutors.